Comparing the Efficacy of a Specialized Package for Women with Body Dysmorphic Disorder and Schema Therapy on Perfectionism and Maladaptive Schemas in Women with Body Dysmorphic Disorder - Rasouli Jazi, Elham; Torkan, Hajar; Yousefi , Zahra (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to compare the efficacy of a specialized package for women with body dysmorphic disorder and schema therapy on perfectionism and maladaptive schemas in women afflicted with body dysmorphic disorder.Methods: The research employed a quasi-experimental design with pre-test, post-test, and follow-up phases involving two experimental groups and one control group, conducted among women with body dysmorphic disorder visiting psychological centers in Isfahan in the first half of 2022. For this purpose, 45 women were selected by convenience and randomly assigned to two experimental groups and one control group. The first experimental group received the specialized package for women with body dysmorphic disorder (researcher-designed), and the second experimental group underwent schema therapy according to the protocol of Young and colleagues (2023) over ten 90-minute sessions, while the control group received no intervention. Participants completed the Perfectionism Questionnaire (1995) and Young's Schema Questionnaire (1998) at pre-test, post-test, and follow-up stages. Data were analyzed using repeated measures ANOVA with SPSS software.Findings: There were significant differences between the groups receiving the specialized package and schema therapy and the control group in terms of negative perfectionism and rejection schemas (p < .01). Additionally, there were differences between the group receiving the specialized package and the schema therapy group in terms of positive perfectionism, autonomy schemas, impaired performance, and impaired limits (p < .01), such that the specialized package had an effect on positive perfectionism, and schema therapy had an impact on autonomy schemas, impaired performance, and impaired limits (p < .05). Moreover, neither treatment had an effect on schemas of other-directedness and hypervigilance.Conclusion: Specialists are recommended to utilize both interventions to improve women with body dysmorphic disorder in terms of reducing negative perfectionism and rejection schemas, to use the specialized package for enhancing positive perfectionism, and to employ schema therapy for reducing autonomy schemas and impaired functioning and limits.